The Effect of Learning Media Utilization to Improve Students’ Learning Motivation on Islamic Education Subject in SMA Dharma Wanita 4 Taman Sidoarjo - nur chomariah chomariah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Keywords: Media, Learning, Motivation Learning media is an important element in teaching and learning process, because it can be loaded messages to be delivered to students either in the form of tools or teaching materials. In addition it is a way to motivate and communicate with students to be more effective, spirit, and enthusiasm in learning activities. Therefore the use of instructional media is needed. This study consists of several problems formulation, such as how the use of media, how the constraints of media use, and how to overcome these obstacles. Type of research in this thesis used qualitative approach. The data collection technique used observation, interview and documentation. While processing and analyzing the data using data which is obtained from the observation, interview, written footage of the documentary, field notes, which is not written in statistical numbers. The research findings in this thesis can be concluded: First: Based on the results of the research showed that by using LKS and LCD projector learning media can improve students' learning motivation on learning Islamic Education in SMA Dharma Wanita 4 Taman Sidoarjo. Second: The constraints that researchers found while using LKS media and LCD Projector on learning Islamic Education in SMA Dharma Wanita 4 Taman Sidoarjo as follows: Unready students in following the lesson at the first meeting by using LKS media, there are students who forget to bring LKS. Third: The efforts which are undertaken as follows: Motivate students to keep the spirit in following the teaching and learning process, advise students to bring their LKS and do not forget it.